Views and perceptions about locally manufactured medicines in Ethiopia: a qualitative study of physicians, patients and regulatory authorities - Chalachew Alemayehu; Geoff Mitchell; Jane Nikles; Abraham Aseffa; Alexandra Clavarino (BMC, 2018)
Abstract Background Because of their cost, the use of locally produced, bioequivalent, generic drugs is universally recommended. In Ethiopia. while the government is committed to raising the market share and use of locally produced drugs, the process is hampered by the lack of a bioequivalence testing centre to strengthen the regulatory environment and deliver quality-assured local medicines. The purpose of this study is to assess the views and perceptions of key regulatory stakeholders, physicians and patients about locally produced generic medicines. Methods A descriptive qualitative study, using focus group discussions and key informant interviews, was conducted. Five key informant interviews (two senior regulatory authority members and 3 institutional review board members) as well as 4 focus group discussions (2 with physicians and 2 with patients) were held. Data were analysed using an inductive, thematic process. Results Four major themes emerged: awareness of lack of bioequivalence profiles associated with local medicines, perceptions about the quality and effectiveness of local medicines, quality and efficacy of imported medicines from developing countries and quality and efficacy of cheaper medicines. All institutional review board members were aware of bioequivalence issues. However, many physicians lacked detailed knowledge about bioequivalence, its clinical relevance and the lack of bioequivalence data for local medicines. All institutional review board members, physicians and male patients, but not female patients, were concerned about the quality and effectiveness of local medicines. Female patients were more confident about the locally produced drugs. In addition, some physicians and patients were not confident about the quality and effectiveness of cheaper drugs and drugs imported from developing countries. Government officials believed that local drugs are reliable. Conclusion The success of promoting the use of inexpensive local medicines and changing the perception of the community depends not only on increasing the domestic market share held by local companies, but also on the capacity of the regulatory environment and companies to produce quality assured medicines and to overcome misconceptions. Among other initiatives, establishing an accredited bioequivalence centre in the country needs to be addressed urgently.